1981
DOI: 10.1017/s0031182000067020
|View full text |Cite
|
Sign up to set email alerts
|

Parasites and the fossil record

Abstract: Parasitologists are fond of alluding to the possible antiquity of their chosen group. They may even place the origin in a specific period of geological time and trace its co-evolution, or lack thereof, with the hosts. These speculations usually make only passing comments on the actual fossil record, but a critical examination suggests that this area can throw much light on both the origins and evolution of parasitism. This review is concerned primarily with the fossil record and its immediate implications. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(34 citation statements)
references
References 42 publications
(41 reference statements)
0
34
0
Order By: Relevance
“…However, some forms of parasitic organism produce galls and cysts on the surface of or inside the host's skeleton, and as such are fairly well represented in the fossil record (Boucot 1990, pp. 59-125;Conway Morris 1981). A number of very rare structures on benthic graptolites have been attributed to parasites.…”
Section: Parasitismmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some forms of parasitic organism produce galls and cysts on the surface of or inside the host's skeleton, and as such are fairly well represented in the fossil record (Boucot 1990, pp. 59-125;Conway Morris 1981). A number of very rare structures on benthic graptolites have been attributed to parasites.…”
Section: Parasitismmentioning
confidence: 99%
“…A number of very rare structures on benthic graptolites have been attributed to parasites. These include expanding, loosely coiled tubular structures or tubothecae (Conway Morris, 1981Morris, , 1990Koslowski, 1970) with a composition and texture identical to normal graptolite cortical tissue (Crowther pers. comm).…”
Section: Parasitismmentioning
confidence: 99%
“…Dickinsoniids are flattened, range to a meter in length, and possess a series of close-set transverse annulations or divisions, separated at a median line across which they alternate (23). Dickinsoniids have been variously assigned to Cnidaria (20), Platyhelminthes (27,30), Annelida (21,31), and an extinct phylum, Proarticulata (23). Runnegar (31) has shown that they are too large to have been flatworms, which lack a circulatory system and rely upon diffusion of oxygen to internal tissues and cannot be much more than 1 mm in thickness.…”
Section: Early Fossil Record Of Body Plansmentioning
confidence: 99%
“…The size, shape and oblique orienta− tion of the tubes are similar to those of trematodes, which are encapsulated by invertebrates such as, for example, in the polychaete shown by Rangel and Santos (2009: fig. 5 Morris 1981Morris , 1988Morris , 1990Ruiz and Lind− berg 1989;Knaust 2009). Nevertheless, Conway Morris (1981: 493) stated that "Pearls in recent molluscs arise from a variety of irritants, but in many instances the sources are trematode larvae".…”
Section: Tests Of the Hypothesesmentioning
confidence: 99%
“…Additionally, even when preserved and detected, the quality of preservation will hamper examination and identifi− cation of such fossil parasitoses. In many cases, only faint traces of the parasite or the damage caused by it can be seen and not much, if anything at all, is known about the parasite it− self (e.g., MacKinnon and Biernat 1970;Welch 1976;Brett 1978;Conway Morris 1981Keupp 1986;Ruiz and Lindberg 1989;Underwood 1993;Bates and Loydell 2000;Lukševics et al 2009). In some other cases, fossil re− mains of invertebrate taxa are occasionally found that are commonly known to represent parasites today (e.g., Waloßek et al , 2006Maas and Waloßek 2001), but where the host is not preserved.…”
Section: Introductionmentioning
confidence: 99%